Estudio del perfil Fitoquímico de los extractos alcohólicos, etéreo y acuoso del Cedrón (aloysia citrodorapaláu). - Panchi Singaucho, Paulo César (2020)
The research project is aimed at studying the phytochemical profile of lemon verbena, for which the leaves and stems were subjected to the drying process at a temperature of 40 ° C for 48 hours, where the usual characteristics were preserved, determining the initial humidity of the plant. plant and the entire drying process until obtaining this constant variable at 10.48%, then a grinding was carried out until a fine powder was extracted from the raw drug to then be packed in plastic bags and sealed under vacuum for its respective analysis. obtained in the extracts the following characteristics: ether extract a density (1,014 g/cm3), viscosity (65.40) mPa, pH (5.46), Acidity (1.463%), Total Solids (14.75 g/100mL-1) and organoleptic characteristics of lemon verbena, alcoholic extract with a density of (0.8445 g/cm3), viscosity (1.5513 mPa); pH (6.6), total solids (11.75) and organoleptic characteristics of lemon verbena, aqueous extract density (1.0001 g/cm3), viscosity (0.9899 mPa), pH (6), total solids (15, 99 g/100mL-1) and organoleptic characteristics of lemon verbena. Once the extracts were obtained, the phytochemical screening of the plant was carried out obtaining the following compounds: fatty compounds, triterpenes / steroids, triterpenes / steroids, catechins, saponins, phenolic compounds, quinones / benzoquinones, reducing sugars, saponins, phenolic compounds, flavonoids, mucilages and bitter principles. Due to the different bioactive compounds in the food industry, lemon verbena can be used as: coloring, preservative, antioxidant, thickener, gelling agent, aroma, flavor, stabilizers, sweeteners.